The Drosophila RNA-binding protein Lark is required for localization of Dmoesin to the oocyte cortex during oogenesis. - McNeil, G.P.; Kaur, M.; Purrier, S.; Kang, R. (Development genes and evolution, 2009)
The RNA-binding protein Lark has an essential maternal role during Drosophila oogenesis. Elimination of maternal expression results in defects in cytoplasmic dumping and actin cytoskeletal organization in nurse cells. The function of this protein is dependent on the activity of one or more N-terminal RNA-binding domains. Here, we report the identification of Dmoesin (Dmoe) as a candidate RNA target of Lark during oogenesis. In addition to actin defects in the nurse cells of lark mutant ovaries, we observed mislocalization of posteriorly localized mRNAs including oskar and germ cell less in the developing oocyte. Anteriorly and dorsally localized mRNAs were not affected. In addition, we observed displacement of the actin cytoskeleton from the oocyte plasma membrane. These phenotypes are reminiscent of mutations in Dmoe and suggested that this RNA maybe a potential target of Lark. We observed a significant decrease in Dmoe protein associated with the membrane of the developing oocyte with no changes in expression or localization within the nurse cells. Evidence for an association between Lark protein and moe RNA during oogenesis comes from results of a microarray-based Ribonomics approach to identify Lark RNA targets. Thus, our results provide evidence that Dmoe RNA is a target of Lark during oogenesis and that it likely regulates either the splicing or translation of this RNA.